ANALISIS RISIKO INFORMATION SYSTEM (IS)/INFORMATION TECHNOLOGY (IT) DENGAN FRAMEWORK ISO 31000:2018 PADA XYZ BOUTIQUE - Crecia; Michael Junius Aguswan; Sri Andayani (P3M STMIK Profesional Makassar, 2024)
Technology is currently developing rapidly and covers almost all fields, one of which is business. XYZ Boutique is a women's clothing business that uses IS/IT in its business activities. However, using technology still has shortcomings and opportunities for business damage. Therefore, this research will analyze IS/IT risks at XYZ Boutique using the ISO 31000:2018 framework. In analyzing risk, data is needed that is collected through interviews and observations with related parties or places. Based on the interview results, 16 risks were obtained and based on the likelihood and impact tables, 5 high risks, 9 medium risks and 2 low risks were obtained. All these risks will be provided with solutions to handle them.